Entrepreneurial leadership, capabilities and firm growth. (February 2015) - Koryak, Oksana; Mole, Kevin F; Lockett, Andy; Hayton, James C; Ucbasaran, Deniz; Hodgkinson, Gerard P
In this article, we review and synthesize extant research on entrepreneurial leadership, capabilities and their influence on the growth of small- and medium-sized enterprises (SMEs). First, we begin by examining the processes, routines and resources underlying substantive growth capabilities; these are capabilities that enable a firm to grow by competing in its market(s) on a day-to-day basis. Second, we explore leadership in terms of the cognitions motivations and decisions to invest in growth. Third, we examine the dynamic capabilities, which extend, modify or create new substantive (growth) capabilities, to support the sustained pursuit of new opportunities. In so doing, we explore the interrelationships between substantial capabilities, leadership and dynamic capabilities. We conclude the review by highlighting areas of consensus and contention in the literature, from which we propose fruitful areas for future research.